PROFESSIONAL AND BUSINESS TOURISM IN UKRAINE –PROSPECTS OF DEVELOPMENT - MOSKVYAK, YAROSLAVA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The large-scale development of the world tourism market, which combines the formation of different types (directions) of tourism and the expansion of the network of tourist destinations, in recent decades has made international tourism one of the key engines of socio-economic progress. And all thanks to the creation of many jobs, a large segment of commercial enterprises, significant profits from foreign trade contracts and infrastructure development. Dynamic development, diversity of social functions and growth of the role of tourism as a branch of the world economy in the context of globalization raise before researchers and practitioners the question of harmonization of tourism with natural, sociocultural, environmental and economic, information and technological capabilities of individual countries and regions and the world economy. in general, ie the need to consider the entire industry of tourism services in terms of the concept of sustainable development. Considers the definitive characteristics of the concept of "professional and business tourism", the main approaches to understanding the concept, the main methods of research of professional and business tourism, the problems of professional and business tourism in Ukraine and prospects for its development, foreign experience of professional and business tourism and opportunities for Ukraine. The analysis of features of development of professional and business tourism in Ukraine and its prospects is carried out. Theoretical and methodological bases of research of professional and business tourism are substantiated. The main approaches to the understanding of professional and business tourism, methods of research of professional and business tourism, methods of research of professional and business tourism are also revealed. Prospects for the development of professional and business tourism in Ukraine, directions of modernization of the sphere of professional and business tourism, foreign experience of professional and business tourism and opportunities for Ukraine are considered.